“ANALISIS PENGARUH MODAL MERJA BERSIH TERHADAP LABA OPERASIONAL PADA INDUSTRI OTOMOTIF PERIODE 2010-2014” - Hana Tamara Putri; Phutri Handayani (Universitas Batanghari Jambi, 2017)
The Background of this researches are to know the development of working capital and operating profit in the automotive industry in 2010-2014 and to measure the impact of Net Working Capital to Operating Profit in the automotive industry the period 2010-2014. Net Working Capital is an analysis of the interrelations between the current assets by current liabilities. Working capital is also called short-term financial management. In a broad perspective, the short-term financial management is the company's efforts to make adjustments to changes in short-term finance; Companies must respond quickly and effectively, operating income is a measure of corporate profits derived from operating activities are still ongoing. The automotive industry is to design, develop, produce, market, and sell the world.In motor vehicles in 2007, more than 73 million motor vehicles, including cars and commercial vehicles manufactured worldwide, In the automotive industry, there are 18 companies consisting of: PT. Astra International Tbk, PT. Astra Otoparts Tbk, PT. Indo Kordsa Tbk, PT. Goodyear Indonesia Tbk, PT. Elephants tungglm PT. Indomobil Sukses International, PT. Indospring Tbk, PT. Multi sejahterah Prima Tbk, PT. Multistrada Arah Sarana Tbk, PT. Nipress Tbk, PT. Prima Alloy Steel Universal Tbk, PT. Congratulations perfect Tbk, PT. Hexindo Adiperkasa Tbk, PT. Indomobil Multi Services Tbk, PT. Intraco Penta Tbk, PT. Tunas Tbk, PT. Kobexindo Tractors Tbk, PT. United Tractor Tbk. The research using descriptive method and uses a simple linear analysis using SPSS 23.0. The results showed that partially Net Working Capital is known that a significant effect on operating profit in the automotive industry, the t test > t table (4.291> 2.03452).Keywords: Net Working Capital, Operating Profit